Analysis of Students’ Knowledge Mastery and Oral Communication Skills Through the Implementation of Think-Pair-Share Model - Mustikawati, Mustikawati; Susilowati, Sri Mulyani Endang; Iswari, Retno Sri (FMIPA UNNES, 2018)
This research aims to analyze the influence of the model Think-Pair-Share (TPS) implementation to knowledge mastery capabilities and oral communication skills of high school students. This is an experimental quasi research with nonequivalent control group design. Population include all students of class X MIPA High School 1 Subah with sample classes X MIPA 1 as experiment class and X MIPA 2 as control class determined by purposive sampling that teacher suggested. The result of t-test shows the significant difference of average posttest grade between experiment and control classes. The increase of learning result experimental class 0,39 (mean), ie from 71,76 become 82,54 while control class 0,18 (low), ie from 70,25 become 75,34. The t-test result also shows a significant difference grade of oral communication skill between the experimental and control classes. The average score of oral communication skill of experiment 78,33, better than control 67,15. This shows that the TPS model has a positive influence on the ability of mastery knowledge and students' oral communication skills. This is supported by the good responses from students and teacher toward model TPS implementation in environmental change learning.